2011
DOI: 10.1007/s10310-010-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses of Salix gracilistyla and Salix subfragilis cuttings to repeated flooding and drought

Abstract: To compare the responses to repeated flooding and drought of Salix gracilistyla, which grows on coarse gravel substrates, and Salix subfragilis, which grows on fine silt or clay substrates, we measured pre-dawn leaf water potential (Ww pd ), osmotic adjustment (Ww tlp , Wo sat ), and biomass production of cuttings under greenhouse conditions. The experimental design involved a control and four treatments that crossed 1 or 3-week flooding (F) with 1 or 2-week droughts (D). Ww pd was reduced after 2 weeks of dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Those authors observed a decrease in the root/shoot ratio as a consequence of prolonged (6 weeks) or cyclical waterlogging (2 weeks of flooding, 2 weeks watered to field capacity, 2 weeks of drought) due to a reduction of the root compartment. A similar root response as a consequence of repeated waterlogging was reported in S. alba(Markus- Michalczyk et al, 2016b) and in S. gracilistyla(Nakai & Kisanuki, 2011). In SmxSa, the observed lack of effects on RB-despite the shorter root length-could be explained, at least in part, by the higher root production rate (number of roots generated as a function of time) reported for this hybrid compared to "Barret 13-44 INTA" clone, either under Control or after waterlogging combined with salinity conditions(Quiñones Martorello et al, 2020).…”
supporting
confidence: 77%
“…Those authors observed a decrease in the root/shoot ratio as a consequence of prolonged (6 weeks) or cyclical waterlogging (2 weeks of flooding, 2 weeks watered to field capacity, 2 weeks of drought) due to a reduction of the root compartment. A similar root response as a consequence of repeated waterlogging was reported in S. alba(Markus- Michalczyk et al, 2016b) and in S. gracilistyla(Nakai & Kisanuki, 2011). In SmxSa, the observed lack of effects on RB-despite the shorter root length-could be explained, at least in part, by the higher root production rate (number of roots generated as a function of time) reported for this hybrid compared to "Barret 13-44 INTA" clone, either under Control or after waterlogging combined with salinity conditions(Quiñones Martorello et al, 2020).…”
supporting
confidence: 77%
“…In poplars, the occurrence of a pre-conditioning flooding period improved waterlogging tolerance (Bejaoui et al 2012). In willows, the combination of drought and flooding has been addressed to a lesser extent than both stresses separately (Nakai et al 2010, Nakai andKisanuki 2011). Some morphological responses to drought are the opposite of those to flooding.…”
mentioning
confidence: 99%
“…Salix subfragilis L. was more tolerant to flooding than Salix gracilistyla Miq. due to higher root ratio under flooding [36]. Salix viminalis L., with a higher dry mass and greater resprouting capacity, had a higher tolerance to tidal flooding than Salix alba L. [37].…”
Section: Introductionmentioning
confidence: 99%
“…Frequent floods may increase tree mortality [65]. Reduced plant survival and growth in response to flooding is common among many species [30,36,66]. An investigation conducted in the TGDR found that S. matsudana and S. variegate were distributed in the water level fluctuation zone and they could endure 210 days of 5 m-deep submergence with a survival rate of 13% and 47%, respectively [62].…”
Section: Growth Response To Periodic Submergencementioning
confidence: 99%